First Report of Stunting and Root Rot of Potato Associated with Pratylenchus penetrans in the Columbia Basin of Washington - Ingham, R E (Plant disease, 2005)
The root-lesion nematode, Pratylenchus penetrans (de Man, 1880) Filipjev, 1936, is a common pathogen of potato in the United States east of the Rocky Mountains and frequently interacts with Verticillium dahliae to aggravate early dying disease (4). West of the Rocky Mountains, P. penetrans is associated with numerous crops including mint, tree, and small fruits but is rarely recovered from potato fields. Pratylenchus neglectus is a common plant-parasitic nematode on potato in the west, but causes little loss in yield and does not usually interact with V. dahliae (1). Management of P. neglectus is generally unnecessary; although a population of P. neglectus from Ontario, Canada appears to be more pathogenic and does interact with V. dahliae (1). During May 2003 (6 weeks after planting), large areas of stunted plants were observed in field inspections and in aerial photographs of two fields (50.6 ha) of cv. Ranger Russet in Benton County, Washington. Lower roots and stolons had numerous, dark lesions that are typical of P. penetrans damage and were severely stunted, while long, white roots had formed abnormally near the soil surface. In early May 2003, lesion nematodes (65 nematodes per 250 g of dry soil and 810 nematodes per g of fresh root weight) recovered from these potato fields were identified as P. penetrans on the basis of morphological characters (2,3). The crop responded to oxamyl (four applications at 1.1 kg of a.i. per ha between early May and mid-July), but the grower estimated that yields were 1.62 tons/ha (4 tons/acre) less than in comparable unaffected fields. To our knoweldge, this is the first report of severe damage to potato from P. penetrans in the Colombia Basin potato-production area. Soil fumigation with Telone II (1,3-dichloropropene) is commonly used in the Columbia Basin to control root-knot (Meloidogyne chitwoodi and M. hapla) and stubby-root (Paratrichodorus allius) nematodes, and metam sodium is used to control V. dahliae. However, since the only nematode recovered from preplant samples was assumed to be P. neglectus, and because cv. Ranger Russet is relatively tolerant to V. dahliae, no fumigant was used in these fields. An increase in mint production in this area may be responsible for introducing P. penetrans into previously uninfested fields since mint is propagated vegetatively and lesion nematodes are commonly associated with mint and could be easily spread in planting material and adhering soil. Identification of P. penetrans in stunted corn from two nearby fields during 2004 suggests that this nematode may be a new and emerging problem in this area. The Columbia Basin is one of the largest potato-producing regions in the United States, and widespread introduction of P. penetrans could add substantial cost to potato production in this area. References: (1) K. Mukerji. No. 458 in: Descriptions of Pathogenic Fungi and Bacteria. CMI, Kew, Surrey, UK, 1975. (2) H. Scheck and S. Koike. Plant Dis. 83:877, 1999